Corrosion behaviour of nickel in dilute nitric acid solution - Kumar A.; Patnaik S.K.; Singh M.M. (My University, 2025)
The corrosion behaviour of nickel in nitric acid solutions of different concentration (1-10%) has been investigated by using electrochemical techniques. The corrosion rate increases with increase in concentration of nitric acid solution. The anodic polarisation curves show active, passive and transpassive behaviour at each concentration and temperature. The results of potential decay and galvanostatic charging experiments indicated the formation of a single oxide film on the nickel surface during its anodic polarisation in nitric acid. An attempt has been made to throw some light on the possible mechanism of nickel corrosion in dilute nitric acid solution on the basis of these results.